(untitled) (Global Journal of Medical Research, 2016)
The Prosthodontic health status and Prosthodontic rehabilitation needs of Jazan local population in the southern region of Saudi Arabia were not well documented. This study evaluates the level of perception and awareness of a group of Jazan population towards Prosthodontic rehabilitation and the factors that prevent them from the treatment. Knowledge and perceived needs of subjects regarding Prosthodontics play an important role in their acceptance to prosthetic rehabilitation. A self-designed questionnaire containing eleven questions was designed and reasons for choosing or refusing treatments were measured using Likert scale. A survey of 467 randomly selected subjects was conducted among the patients and relatives reported to the College of Dentistry, Jazan University, Jazan. Collected data were statistically analysed using SPSS V.19 for descriptive statistics along with Chi-squared test at a significance level of p < 0.05.